A PHANTOM STUDY TO DETERMINE THE OPTIMAL PLACEMENT OF EYE DOSEMETERS ON INTERVENTIONAL CARDIOLOGY STAFF. Issue 4 (13th March 2019) - Ishii, H; Chida, K; Satsurai, K; Haga, Y; Kaga, Y; Abe, M; Inaba, Y; Zuguchi, M
Abstract: The International Commission on Radiological Protection has substantially reduced the recommended maximum annual eye lens dose for workers. Use of a dedicated eye dosemeter is one method for accurate dose monitoring. The main aim of this study was to yield recommendations for optimal placement of eye dosemeters to estimate the eye dose to interventional cardiology physicians and nurses. A phantom measurement was conducted to simulate typical interventional cardiology procedures. Considering eight X-ray tube angulations, the left side of the head position provide good estimates for physician, and the forehead position provide good estimates for nurse.